2015
DOI: 10.1164/rccm.201503-0444oc
|View full text |Cite
|
Sign up to set email alerts
|

Semiquantitative Culture Analysis during Therapy for Mycobacterium avium Complex Lung Disease

Abstract: Rationale: Microbiologically based criteria such as sputum culture conversion to negative have traditionally been used to define treatment success for mycobacterial diseases. There are, however, limited data regarding whether nontuberculous mycobacterial sputum culture conversion or semiquantitative culture analysis correlates with subjective or nonmicrobiologic objective indices of treatment response.Objectives: To determine whether a semiquantitative mycobacterial culture scale correlated with clinical disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 22 publications
3
44
1
Order By: Relevance
“…However, this study demonstrated a significant decrease in the positivity of semiquantitative sputum cultures for AFB over the course of treatment with CFZ in both the initial treatment and salvage treatment groups, suggesting that CFZ-containing regimens can help to decrease the mycobacterial burden. Semiquantitative AFB culture positivity is likely to reflect disease burden and was used to assess microbiological responses to the treatment of NTM lung disease in some recently reported studies (38)(39)(40). Given that M. abscessus lung disease is regarded as a chronic, incurable infection and that there are limited antibiotic options, improvement in the health-related quality of life is a reasonable treatment goal, especially in refractory cases (32).…”
Section: Discussionmentioning
confidence: 99%
“…However, this study demonstrated a significant decrease in the positivity of semiquantitative sputum cultures for AFB over the course of treatment with CFZ in both the initial treatment and salvage treatment groups, suggesting that CFZ-containing regimens can help to decrease the mycobacterial burden. Semiquantitative AFB culture positivity is likely to reflect disease burden and was used to assess microbiological responses to the treatment of NTM lung disease in some recently reported studies (38)(39)(40). Given that M. abscessus lung disease is regarded as a chronic, incurable infection and that there are limited antibiotic options, improvement in the health-related quality of life is a reasonable treatment goal, especially in refractory cases (32).…”
Section: Discussionmentioning
confidence: 99%
“…While there are no prospective studies indicating which clinical endpoints are most informative during and following treatment for NTM-pulmonary disease, a large retrospective case series involving patients on treatment for MAC-pulmonary disease provides some insights 185. Almost all patients presented with cough, sputum production and fatigue, and patients whose cough improved while prescribed NTM treatment were more likely to culture-convert (p<0.001).…”
Section: Section 12d: What Antibiotic Regimen Should Be Used To Treatmentioning
confidence: 99%
“…For example, an article published in 2015 suggested that changes in a baseline score derived from the semiquantitative measure of MAI growth over a 3‐month period was highly predictive of long‐term sputum conversion and treatment success in pulmonary MAI 7. Regarding pneumonias and other opacities seen on chest imaging of patients at risk for lung cancer, recommendations have suggested follow‐up radiographs or CT scans in 6‐12 weeks post pneumonia treatment to ensure resolution.…”
Section: Discussionmentioning
confidence: 99%